Some issues affecting higher education in the English-speaking Caribbean - The case of the University of the West Indies - Hunte, Keith D. (1987)
This paper examines some of the results achieved by The University of the West Indies (UWI) in trying to meet some of the needs of its 14 Caribbean member countries in the area of higher education and research
An adaptation of a paper entitled "Education and Development in the English-speaking Caribbean" which was delivered at the Inauguration of the Centre for Caribbean and Latin American Studies at State University of New York, Albany, in April 1985
Keywords: The University of the West Indies